Efforts to Increase Public Awareness of Historical Artifacts at the Kutho Kedawung Site in Paleran Umbulsari Village Jember Regency - Nurhidayati, Titin; Rofiq, M. Nafiur; Millah, Izzatul; Mubarokah, Lailatul; Wahyuni, Wahyuni; Kurniawan, Rif’an (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The community service program (PKM-BR) aims to enhance public awareness and engagement in preserving historical artifacts from the Majapahit Kingdom, focusing on the Kutho Kedawung Site in Paleran Village. It seeks to motivate individuals to understand and protect cultural heritage within their locality. Method: The program involves socialization activities conducted by students to educate and involve the community in preserving cultural heritage. It includes pre-activity assessments, evaluations during activities, and post-activity assessments to document information about Kutho Kedawung, utilizing both oral traditions and data. Practical Applications: The research results encourage community involvement in safeguarding historical sites, highlighting the significance of preserving cultural heritage. This can lead to greater appreciation and protection of historical artifacts, contributing to the conservation of cultural heritage for future generations. Conclusion: The study underscores the importance of community engagement in preserving historical artifacts, particularly within the context of the Majapahit Kingdom. It emphasizes the practical implications of enhancing public awareness and involvement in cultural heritage preservation efforts.